Comparative ethical evaluation of epigenome editing and genome editing in medicine: first steps and future directions - Alex, Karla; Winkler, Eva C. (Journal of medical ethics, 2024)
Targeted modifications of the human epigenome, epigenome editing (EE), are around the corner. For EE, techniques similar to genome editing (GE) techniques are used. While in GE the genetic information is changed by directly modifying DNA, intervening in the epigenome requires modifying the configuration of DNA, for example, how it is folded. This does not come with alterations in the base sequence (‘genetic code’). To date, there is almost no ethical debate about EE, whereas the discussions about GE are voluminous. Our article introduces EE into bioethics by translating knowledge from science to ethics and by comparing the risks of EE with those of GE. We, first (I), make the case that a broader ethical debate on EE is due, provide scientific background on EE, compile potential use-cases and recap previous debates. We then (II) compare EE and GE and suggest that the severity of risks of novel gene technologies depends on three factors: (i) the choice of an ex vivo versus an in vivo editing approach, (ii) the time of intervention and intervention windows and (iii) the targeted diseases. Moreover, we show why germline EE is not effective and reject the position of strong epigenetic determinism. We conclude that EE is not always ethically preferable to GE in terms of risks, and end with suggestions for next steps in the current ethical debate on EE by briefly introducing ethical challenges of new areas of preventive applications of EE (III).